Band select ultra wide band unequal power splitter. Issue 7 (23rd April 2016) - Packiaraj, D.; Ramesh, M.; Kalghatgi, A.T.
ABSTRACT: In this letter, a new design of a band select ultra wide band (UWB) unequal power splitter suitable for broadband communication systems was presented. To obtain band select characteristics, the proposed structure used broadside coupled lines. The quarter wave transformer in the conventional Wilkinson power splitter was replaced by offset broadside coupled lines to achieve broadband operation in this letter. The broadside coupled line configuration was achieved between the transmission lines in the top layer and a floating conductor in the defected ground plane of the microstrip medium. The advantage of this type of power splitter was that it could reject the out of band frequency signals. The proposed two way UWB unequal power splitter was designed using microstrip medium with defected ground structure for a wide range of frequencies between 3.1 and 8 GHz. Experimental results of the designed unequal power splitter (10 and 0.5dB) have been verified against the results full wave simulations and the results were in good agreement. The amplitude variation over the frequency band was within ±0.3 dB. The isolation between the output ports was more than 19 dB. Size of the realized power splitter was 36 mm × 40 mm × 0.78 mm. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1563–1566, 2016